Peer Crowd Identification of Young and Early Middle Adulthood Customers at Vape Shops. (September 2021) - Sussman, Steve; Galimov, Artur; Meza, Leah; Huh, Jimi; Baezconde-Garbanati, Lourdes; Pokhrel, Pallav
Vape shops specialize in the sales of e-cigarettes and other vaping products. In recent studies, young adults who use e-cigarettes have tended to identify with at-risk peer crowds. This is the first study to examine vape shop customers' clientele. Composed primarily of young adults and persons in early middle adulthood, we speculated that a relatively high prevalence of those who appeared to bystanders as radical/extreme (at-risk) customers would be identified as such at these shops. We recruited vape shops throughout Southern California (N = 44 shops), and trained teams of data collectors visited each of the consented vape shops, making note of 451 customers' appearance, including features such as manner of dress, presence of tattoos, and hairstyles. Customers were then coded as either belonging to a conventional, progressive, or radical/extreme crowd based on outward appearance. Of the customers observed, 223 (49%) were rated as appearing to be in the conventional crowd; 169 (38%) were rated as appearing to be in the progressive crowd, and only 59 (13%) were rated as appearing to be in the radical/extreme crowd. The conventional crowd tended to appear older. Clientele may reflect that more conventional young and early middle age adults are tempted to visit vape shops due to perceptions of greater acceptability or safety of e-cigarettes. E-cigarette mass media campaigns aimed at protecting potential vape shop customers from harm may need to depict more conservative-looking characters.